2020
DOI: 10.3390/ijerph17062107
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Accuracy of Implant Installation with a Navigation System (NS), a Laboratory Guide (LG), NS with LG, and Freehand Drilling

Abstract: The aim of this study was to compare the accuracy of implant placement by using the conventional freehand method, the surgical guide alone, the dental navigation system alone, and the dental navigation system with a surgical guide. The participants were aged 20 years or older and were requiring dental implant surgery according to an assessment made by a dentist between July 2014 and December 2017. A total of 128 dental implants were inserted, 32 dental implants in each group, and participants with similar or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
8
29
0
5
Order By: Relevance
“…Nevertheless, it should be taken into account that 4 of the 5 clinical studies [43,44,50,51] were conducted by the same research group. A similar situation was found for several systems (AqNavi system [49,59,62], Iris-100 system [47,52], and ImplaNav [46,53]) since most published studies were performed by the same authors. X-guide (X-Guide, X-Nav Technologies, LLC, Lansdale, Pa) had the largest cohort of patients (almost 500 cases with more than 700 implants placed) [48], and some clinical data was also available for AqNavi (AQNavi, TITC Ltd, Kaohsiung, Taiwan) and ImplaNav (ImplaNav; BresMedical, Sydney, Australia), as they each had at least one clinical study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Nevertheless, it should be taken into account that 4 of the 5 clinical studies [43,44,50,51] were conducted by the same research group. A similar situation was found for several systems (AqNavi system [49,59,62], Iris-100 system [47,52], and ImplaNav [46,53]) since most published studies were performed by the same authors. X-guide (X-Guide, X-Nav Technologies, LLC, Lansdale, Pa) had the largest cohort of patients (almost 500 cases with more than 700 implants placed) [48], and some clinical data was also available for AqNavi (AQNavi, TITC Ltd, Kaohsiung, Taiwan) and ImplaNav (ImplaNav; BresMedical, Sydney, Australia), as they each had at least one clinical study.…”
Section: Discussionsupporting
confidence: 73%
“…Figure 2 shows the complete flowchart of the study selection process. Of the 24 articles, 10 reported on clinical studies involving humans [43][44][45][46][47][48][49][50][51][52] and 14 reported on preclinical "in vitro" studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The types of studies included for each system can be observed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A aplicação da robótica na cirurgia se mostrou eficaz em implantodontia, no tratamento de câncer de cabeça e pescoço, tratamento de neuralgia do trigêmeo e tratamento de pequenas lesões no seio piriforme e osteotomias, de acordo com os estudos de Reddy et al (2015) e Mazerolle et al (2018). Além das aplicações práticas já citadas, Sun et al (2020), Ghai, et al (2018) e Kim et al (2016) também ressaltam a eficácia da robótica no planejamento cirúrgico, através do VSP (Virtual Surgical Planning) e da impressão 3D de modelos anatômicos.…”
Section: Discussionunclassified
“…As cirurgias com a presença de robôs são indicadas em diversos tipos de procedimentos na odontologia, principalmente em intervenções complexas que necessitam de uma alta precisão ou de resultados funcionais e estéticos superiores às cirurgias convencionais, ou intervenções nas quais antes o procedimento não era possível, como pode-se ver nas citações de autores como Sun et al (2020), Alfouzan et al (2018), Gulati et al (2015), Reddy et al(2015) e Kumar et al (2016).…”
Section: Discussionunclassified